Barriers and facilitators to ART adherence among ART non-adherence people living with HIV in Cameroon: A qualitative phenomenological study - Buh, Amos; Deonandan, Raywat; Gomes, James; Krentel, Alison; Oladimeji, Olanrewaju; Yaya, Sanni (Université d'Ottawa | University of Ottawa, 2023)
Antiretroviral therapy (ART) needs to be taken for life with near perfect levels of adherence for it to be effective. Nonetheless, ART non-adherence is still observed in sub-Saharan African (SSA) countries such as Cameroon. The objective of this study was to assess the factors influencing non-adherence and or adherence among people living with HIV (PLWH) who have experienced non-adherence to ART in Cameroon.
Keywords: Female; Humans; Adult; Male; Cameroon; Qualitative Research; Data Collection; Focus Groups; Medicine, Traditional